Implementation of Rainwater Harvesting Integrated Farming to realize Sustainable Development Goals (SDGs) - Shafa Wibowo, Salsabila; Dhani Nur Amirah, Sausan; Khairunnisa, Shafira Intan; Yumaroh, Siti; Tadzkiroh, Ummi; Herawati, Vania Dewi; Rahmadhani, Vika Ayu; Putri, Yanuar Satari; Nisa, Zaenab Ulyatun; Kurniawati, Zeny; Putro , Sartono (Universitas Muhammadiyah Surakarta, 2022)
One of the SDGs elements related to the fulfillment of access to clean drinking water and sanitation must be achieved by the world community by 2030. The purpose of this research was to implement a rainwater harvesting system integrated with agriculture and livestock for alternative clean water needs in Jatikuwung Village. This research used the Research and Development (R&D) method. The model used in this research is the ADDIE model. This ADDIE model has 5 stages, namely (1) Analysis: analyzing the situation, (2) Design: designing for product design to be made, (3) Development: producing or making products, (4) Implementation: implementing of limited product testing in the field, and (5) Evaluation: evaluating the cycles and end-product. This research was conducted in Jatikuwung Village. This location experiences a water crisis during the dry season. The subject of this research was designing Rainwater Harvesting Integrated Farming by KKN-T students in Jatikuwung village. The object of this research is the process of Rainwater Harvesting Integrated Farming flow that can be utilized in life. This research was conducted in October-November 2022 and was limited to the development stage. The results of this research were rainwater harvesting integrated farming through a rainwater harvesting system that produced clean water. This system can be useful for life integrated with catfish farms that get food from maggots, and water in catfish flows to plants.